The Single Nucleotide Polymorphisms of AP1S1 are Associated with Risk of Esophageal Squamous Cell Carcinoma in Chinese Population - Su F; Fang Y; Yu J; Jiang T; Lin S; Zhang S; Lv L; Long T; Pan H; Qi J; Zhou Q; Tang W; et al. (Dove Medical Press, 2022)
Feng Su,1,* Yong Fang,1,* Jinjie Yu,1 Tian Jiang,1 Siyun Lin,1 Shaoyuan Zhang,1 Lu Lv,2 Tao Long,2 Huiwen Pan,2 Junqing Qi,2 Qiang Zhou,3 Weifeng Tang,4 Guowen Ding,2 Liming Wang,5 Lijie Tan,1 Jun Yin1 1Department of Thoracic Surgery, Zhongshan Hospital of Fudan University, Shanghai, People's Republic of China; 2Department of Cardiothoracic Surgery, Affiliated People's Hospital of Jiangsu University, Jiangsu, People's Republic of China; 3Department of Thoracic Surgery, Sichuan Cancer Hospital & Institute, Sichuan, People's Republic of China; 4Department of Cardiothoracic Surgery, Nanjing Drum Tower Hospital, Jiangsu, People's Republic of China; 5Department of Respiratory, Shanghai Xuhui Central Hospital, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Jun Yin; Lijie Tan, Zhongshan Hospital of Fudan University, 180 Fenglin road, Xuhui District, Shanghai, 200032, People's Republic of China, Email jun_yin@fudan.edu.cn; tan.lijie@zs-hospital.sh.cnBackground: The σ 1A subunit of the adaptor protein 1 (AP1S1) participates in various intracellular transport pathways, especially the maintenance of copper homeostasis, which is pivotal in carcinogenesis. It is therefore rational to presume that AP1S1 might also be involved in carcinogenesis. In this hospital-based case-control study, we investigated the genetic susceptibility to ESCC in relation to SNPs of AP1S1 among Chinese population.Methods: A database containing a total of 1303 controls and 1043 ESCC patients were retrospectively studied. The AP1S1 SNPs were analyzed based on ligation detection reaction (LDR) method. Then, the relationship between ESCC and SNPs of AP1S1 was determined with a significant crude P< 0.05. Then the logistic regression analysis was used for the calculation for adjusted P in the demographic stratification comparison if a significant difference was observed in the previous step.Results: AP1S1 rs77387752 C>T genotype TT was an independent risk factor for ESCC, while rs4729666 C>T genotype TC and rs35208462 C>T genotype TC were associated with a lower risk for ESCC, especially in co-dominant model and allelic test for younger, male subjects who are not alcohol-drinkers nor cigarette smokers.Conclusion: AP1S1 rs77387752, rs4729666 and rs35208462 polymorphisms are associated with susceptibility to ESCC in Chinese individuals. AP1S1 SNPs may exert an important role in esophageal carcinogenesis and could serve as potential diagnostic biomarkers.Keywords: AP1S1, single nucleotide polymorphism, SNP, esophageal squamous cell carcinoma, ESCC